2022
DOI: 10.3390/vaccines11010024
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of COVID-19 Vaccines in Adults with Diabetes Mellitus: A Systematic Review

Abstract: Persons with diabetes mellitus may have an increased risk of severe illness or death from COVID-19 compared to persons without diabetes. Prior studies indicate that immune response and thus vaccine effectiveness might be lower in persons with diabetes. We aimed to systematically review the effectiveness of COVID-19 vaccines in adults with diabetes. Pubmed, Embase, Web of Science and Cochrane Library were searched for studies that evaluated the effectiveness of COVID-19 vaccines in adults with diabetes, publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
1
14
1
Order By: Relevance
“…Several previous studies conducted on COVID-19 vaccines’ immunogenicity and effectiveness in patients with diabetes compared to healthy controls. Most of these studies have reported lower vaccine effectiveness and immunogenicity in patients with diabetes when compared to healthy controls [ 27 , 28 ]. However, our study yielded different results, which could be attributed to various factors, such as the type of COVID-19 vaccine used, sample size, levels of glycaemic control and characteristics of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies conducted on COVID-19 vaccines’ immunogenicity and effectiveness in patients with diabetes compared to healthy controls. Most of these studies have reported lower vaccine effectiveness and immunogenicity in patients with diabetes when compared to healthy controls [ 27 , 28 ]. However, our study yielded different results, which could be attributed to various factors, such as the type of COVID-19 vaccine used, sample size, levels of glycaemic control and characteristics of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Immunogenicity of vaccines appear to be lower in people with diabetes irrespective of the type of vaccine and weaker with higher BMI and worse glucose control [49] . People with diabetes have relatively less protection against infection, hospitalization, severe disease and death [50] . However, these data are derived from observational studies with high risk of bias.…”
Section: Preventing and Managing Covid-19 In People With Metabolic Sy...mentioning
confidence: 99%
“…A recent systematic review by van den Berg et al 119 -7 of 14 be performed due to the vast heterogeneity of the studies, vaccine effectiveness appeared to be generally lower in people with diabetes compared with the general population or people without diabetes.…”
Section: Covid-19 Vaccination and Diabetesmentioning
confidence: 99%
“…Nevertheless, vaccination is still highly effective in this population, and no differences in mortality prevention have been observed. 119 It has come to light that poor glycaemic control may impair the immune response to vaccination. 115,121 Further studies are required to confirm this association; however, considering the existing evidence for poor glycaemic control compounding adverse outcomes COVID-19, careful monitoring and optimisation of glycaemic control is advised.…”
Section: Are Vaccines Efficacious In Diabetes?mentioning
confidence: 99%
See 1 more Smart Citation